First report of Anisakis sp. in Epinephelus sp. in East Indonesia - Detha, Annytha Ina Rohi; Wuri, Diana Agustiani; Almet, Julianty; Riwu, Yuni; Melky, Christin (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present research was conducted to identify the prevalence of Anisakis sp. as fish-borne zoonoses in Epinephelus sp. in territorial waters of East Nusa Tenggara, Indonesia. Materials and methods: A total of 50 fish (Epinephelus sp.) were collected from Kupang Fish Market in East Nusa Tenggara. Identification of Anisakis sp. was performed based on morphological observations considering shape of ventriculus, boring tooth, and mucron using binocular microscope. Results: Prevalence of Anisakis sp. in Epinephelus sp. was 22% (n=11/50). The parasite was mostly found in abdominal cavity, gonad, intestines, and muscles of fish. Conclusion: This study suggests that Anisakis sp. is present in Epinephelus sp., exerting potential health hazards for human who consume the fish. http://doi.org/10.5455/javar.2018.e241